Measuring eye deformation between planning and proton beam therapy position using magnetic resonance imaging. (October 2020) - Jaarsma-Coes, Myriam G.; Marinkovic, Marina; Astreinidou, Eleftheria; Schuurmans, Megan S.; Peters, Femke P.; Luyten, Gregorius P.M.; Rasch, Coen R.N.; Beenakker, Jan-Willem M.
Highlights: Eye and tumour deformation due to gravity is less than 0.4 mm. Conformity index between flexed and supine position for eyes is >0.95. Conformity index between flexed and supine position for tumours is >0.85. Supinely acquired MR images can be used for PBT planning. Abstract: Proton beam therapy (PBT) for uveal melanoma (UM) is performed in sitting position, while the acquisition of the Magnetic resonance (MR)-images for treatment planning is performed in supine position. We assessed the effect of this difference in position on the eye- and tumour- shape. Seven subjects and six UM-patients were scanned in supine and a seating mimicking position. The distances between the tumour/sclera in both positions were calculated. The median distance between both positions was 0.1 mm. Change in gravity direction produced no substantial changes in sclera and tumour shape, indicating that supinely acquired MR-images can be used to plan ocular-PBT.